Microendoscopy-assisted extraforaminal lumbar interbody fusion for treating single-level spondylodesis - Motohide Shibayama; GuangHua Li; LiGuo Zhu; Zenya Ito; Fujio Ito (International Journal of Spine Research - Peertechz Publications, 2020)
Study design: technical note, retrospective case series. Objectives: Lumbar interbody fusion is a standard technique for treating degenerative lumbar disorders involving instability. Due to its invasiveness, a minimally invasive technique, Extraforaminal Lumbar Interbody Fusion (ELIF), was introduced. On surgically approaching posterolaterally, the posterior muscles and spinal canal are barely invaded. Despite its theoretical advantage, ELIF is technically demanding and has not been popularised. Therefore, we developed a microendoscopy-assisted ELIF (mELIF) technique which was designed to be safe and less invasive. Here, we aimed to report on the surgical technique and clinical results. Methods: Using a posterolateral approach similar to that of lateral disc herniation surgery, a tubular retractor, 16 or 18 mm in diameter, was placed at the lateral aspect of the facet joint. The facet joint was partially excised, and the disc space was cleaned. A cage and local bone graft were inserted into the disc space. All disc-related procedures were performed under microendoscopy. The spinal canal was not invaded. Bilateral percutaneous screw-rod constructs were inserted and fixed.  Results: Fifty-five patients underwent the procedure. The Oswestry Disability Index and visual analogue scale scores greatly improved. Over 90% of the patients obtained excellent or good results based on Macnab's criteria. There were neither major adverse clinical effects nor the need for additional surgery. Conclusions: mELIF is minimally invasive because the spinal canal and posterior muscles are barely invaded. It produces good clinical results with fewer complications. This technique can be applied in most single-level spondylodesis cases, including those involving L5/S1 disorders.